2020
DOI: 10.5435/jaaosglobal-d-20-00034
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Patient-reported Outcomes in a Total Joint Arthroplasty Program at a High-volume Academic Medical Center

Abstract: Introduction: Despite widely appreciated barriers to successful clinical implementation, the literature regarding how to operationalize electronic health record-integrated patient-reported outcomes (PROs) remains sparse. We offer a detailed summary of the implementation of PROs into the standard of care at a major tertiary academic medical center. Methods: Collection of four Patient-Reported Outcomes Measurement Information System computer adaptive tests was piloted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Our most notable challenge was increasing our overall response rate for PROMs collection; our rate for all patients (29%) was consistent with the statistic for general surveys (33%) [ 28 ], and our rate was slightly higher for patients who were MyChart active (42%). The variation we reported in our study is consistent with other PROMs collection initiatives reported in orthopedics (34–77% over a 1-year period [ 20 ]. However, the general response rate for PROMs collection initiatives in orthopedics appears to hover around 70–80%, with studies reporting 74.9% [ 29 ] and 72.6% [ 30 ], and the UK National Joint Registry reporting 64%, the Swedish Hip Arthroplasty Registry 79%, and the New Zealand Joint Registry 70% [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our most notable challenge was increasing our overall response rate for PROMs collection; our rate for all patients (29%) was consistent with the statistic for general surveys (33%) [ 28 ], and our rate was slightly higher for patients who were MyChart active (42%). The variation we reported in our study is consistent with other PROMs collection initiatives reported in orthopedics (34–77% over a 1-year period [ 20 ]. However, the general response rate for PROMs collection initiatives in orthopedics appears to hover around 70–80%, with studies reporting 74.9% [ 29 ] and 72.6% [ 30 ], and the UK National Joint Registry reporting 64%, the Swedish Hip Arthroplasty Registry 79%, and the New Zealand Joint Registry 70% [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…The decision-making process and challenges we faced with our initiative are similar to other studies reporting the implementation of PROMs collection. With our implementation approach we were able to successfully administer, collect, and report PROMs within the EHR and through data visualization applications as other studies in orthopedic settings have demonstrated [ 20 – 22 ]. Moreover, we decided to collect PROMIS measures as our standard measure, as opposed to region-specific or legacy measures associated with each clinical division, which allowed us to scale the collection of PROMs across our department while minimizing the complexity of EHR programming for administering and reporting our PROMs.…”
Section: Discussionmentioning
confidence: 99%
“…Like other CAT implementation studies, 13 , 26 , 27 our GlauCAT tests took, on average, 1.5 to 3 minutes to complete, highlighting the effectiveness of CAT in delivering efficient, low-burden PROM measurement. Indeed, GlauCAT provided 6 important QOL outcomes in <10 minutes (median), which compares promisingly with many paper-pencil PROMs that provide only 1 to 2 outcomes in a similar amount of time.…”
Section: Discussionmentioning
confidence: 63%
“…Integration with EMR is a known barrier to PROM implementation due to interoperability and system infrastructure issues. 34 However, several studies 13 , 27 have managed to overcome these technical barriers through dedicated information technology and software programmer teams. Enabling patients to complete the GlauCAT tests at home via a secure automated link is planned, which is especially pertinent in the era of coronavirus disease 2019 (COVID-19), where patients are reluctant to attend the clinic or share tablets.…”
Section: Discussionmentioning
confidence: 99%
“…Third, to enable reach to diverse patients in terms of cancer and cancer treatment, the PRO system should be implemented in all departments of a cancer center. This will require comprehensive training within and across departments to ensure the active support of cancer care teams, which in turn may increase screener completion rates [ 50 ]. Finally, the outreach protocol triggered by a positive screen must be efficient and timely to ensure rapid connection to treatment.…”
Section: Discussionmentioning
confidence: 99%